Cortical multisensory connectivity is present near birth in humans - Sours, Chandler; Raghavan, Prashant; Foxworthy, W. Alex; Meredith, M. Alex; El Metwally, Dina; Zhuo, Jiachen; Gilmore, John H.; Medina, Alexandre E.; Gullapalli, Rao P. (Brain imaging and behavior, 2017)
How the newborn brain adapts to its new multisensory environment has been a subject of debate. Although an early theory proposed that the brain acquires multisensory features as a result of postnatal experience, recent studies have demonstrated that the neonatal brain is already capable of processing multisensory information. For multisensory processing to be functional, it is a prerequisite that multisensory convergence among neural connections occur. However, multisensory connectivity has not been examined in human neonates nor are its location(s) or afferent sources understood. We used resting state functional MRI (fMRI) in two independent cohorts of infants to examine the functional connectivity of two cortical areas known to be multisensory in adults: the intraparietal sulcus (IPS) and the superior temporal sulcus (STS). In the neonate, the IPS was found to demonstrate significant functional connectivity with visual association and somatosensory association areas, while the STS showed significant functional connectivity with the visual association areas, primary auditory cortex, and somatosensory association areas. Our findings establish that each of these areas displays functional communication with cortical regions representing various sensory modalities. This demonstrates the presence of cortical areas with converging sensory inputs, representing that the functional architecture needed for multisensory processing is already present within the first weeks of life.